2021
DOI: 10.3389/fphar.2021.700454
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Omics, Immune Infiltration, and Pharmacogenomic for SENP1 in the Pan-Cancer Cohort

Abstract: Sentrin specific-protease 1 (SENP1) is a protein involved in deSUMOylation that is almost overexpressed in cancer. SENP1 has a determinative role in the activation of transcription programs in the innate immune responses and the development B of and C lymphocytes. We found, SENP1 possibly plays a critical role in immune infiltration and acts as an expression marker in PAAD, ESCA, and THYM. CD4+ T cells, CD8+ T cells, and macrophages were more key-related immune cells, indicating that SENP1 might be introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 143 publications
0
8
0
Order By: Relevance
“…However, the oncogenic role of PTBP3 in various human tumours remains unclear. A pan-cancer analysis can identify the difference between normal and tumour tissues, providing a comprehensive understanding of the molecular mechanisms of tumorigenesis and progression ( Chakravorty et al, 2019 ; Chai et al, 2020 ; Chen et al, 2021 ; Fiala et al, 2021 ; Taghvaei et al, 2021 ). Thus, we performed a pan-cancer analysis of the gene expression profile, survival status, genetic alteration, protein phosphorylation, immune infiltration, N6-methyladenosine, and relevant cellular pathways of PTBP3 in various human tumours based on the TCGA, GEO, and CPTAC databases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the oncogenic role of PTBP3 in various human tumours remains unclear. A pan-cancer analysis can identify the difference between normal and tumour tissues, providing a comprehensive understanding of the molecular mechanisms of tumorigenesis and progression ( Chakravorty et al, 2019 ; Chai et al, 2020 ; Chen et al, 2021 ; Fiala et al, 2021 ; Taghvaei et al, 2021 ). Thus, we performed a pan-cancer analysis of the gene expression profile, survival status, genetic alteration, protein phosphorylation, immune infiltration, N6-methyladenosine, and relevant cellular pathways of PTBP3 in various human tumours based on the TCGA, GEO, and CPTAC databases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our data suggest that miR-16-5p can inhibit T cell proliferation by regulating Ca 2+ influx, resulting in the poor recovery of CD4 + T cell counts during ART. Other miRNAs in the panel, such as miR-138-5p, have been reported to be related to immune regulation in tumors and the inflammatory response (84)(85)(86). The expression of miR-323-3p was high in T cells producing inflammatory factors (e.g., interleukin (IL)-17 and IL-22) ( 87), which suggests it may have potential roles in regulating the immune response in HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there is an association between SENP1 expression and cancer immunity, suggesting that SENP1 could be used as a cancer immunotherapy target. SENP1 also correlates with immune infiltration, and a variety of transcription factors involved in regulation of apoptosis, proliferation, cell cycle, tumorigenesis, invasion and metastasis are responsible of the increased expression of SENP1 in cancer cells [ 138 ]. Among them is YY1, which, a few years ago, was shown to form a complex with the chromatin adaptor BRD4 to regulate Senp1 expression [ 139 ].…”
Section: Sumo Proteases In Cancermentioning
confidence: 99%
“…SENP1 depletion in multiple myeloma (MM) cells has been shown to decrease viability and proliferation, while inducing apoptosis, which correlates with inactivation of NF-κB signaling [ 103 ]. SENP1 also shows high correlation with sensitivity and resistance to anti-cancer drug and drug targeted genes [ 138 ]. For instance, SENP1 has been shown to reduce cisplatin sensitivity of hypoxic ovarian cancer cells [ 104 ].…”
Section: Sumo Proteases In Cancermentioning
confidence: 99%